New suns 2 : original speculative fiction by people of color - Shawl, Nisi (Solaris, 2023)
New Suns 2 brings you fresh visions of the strange, the unexpected, the shocking--breakthrough stories, stories shining with emerging truths, stories that pierce stale preconceptions with their beauty and bravery. Like the first New Suns anthology (winner of the World Fantasy, Locus, IGNYTE, and British Fantasy awards), this book liberates writers of many races to tell us tales no one has ever told. Many things come in twos: dualities, binaries, halves, and alternates. Twos are found throughout New Suns 2, in eighteen science fiction, fantasy, and horror stories revealing daring futures, hidden pasts, and present-day worlds filled with unmapped wonders. Including stories by Daniel H. Wilson, K. Tempest Bradford, Darcie Little Badger, Geetanjali Vandemark, John Chu, Nghi Vo, Tananarive Due, Alex Jennings, Karin Lowachee, Saad Hossain, Hiromi Goto, Minsoo Kang, Tlotlo Tsamaase, Rochita Loenen-Ruiz, Malka Older, Kathleen Alcalá, Christopher Caldwell and Jaymee Goh with a foreword by Walter Mosley and an afterword by Dr. Grace Dillon.--Amazon